A Challenge for a Unique Dengue Vector Control Programme: Assessment of the Spatial Variation of Insecticide Resistance Status amongst Aedes aegypti and Aedes albopictus Populations in Gampaha District, Sri Lanka - Dalpadado, Rasika (Biomed Res Int, 2021)
BACKGROUND: To date, dengue is considered an important public health problem in Sri Lanka. Irrational use of insecticides without evidence-based applications has primed the development of resistance in mosquito vectors. METHOD: The present study investigated the resistance status of Aedes aegypti and Aedes albopictus to commonly used insecticides in three selected Medical Officer of Health (MOH) areas (i.e., Attanagalla, Dompe, and Negombo) in Gampaha District, Western Province of Sri Lanka. Entomological surveys were performed using ovitraps and larval collections. Larval bioassays were carried out to determine the LC(50), LC(90), and LC(95) and susceptibility status for organophosphate temephos, whereas adult bioassays were performed to test the 0.03% deltamethrin and 0.8% malathion susceptibility. RESULTS: The study revealed that the temephos concentrations required to control Ae. aegypti (13.7-17.7 times) and Ae. albopictus (4.6-7.6 times) are higher than the diagnostic concentration (0.012 mg/L) proposed by the World Health Organization. The highest resistance levels were observed for both Ae. aegypti (14 ± 1.87) and Ae. albopictus (36 ± 1.87) collected from the Negombo MOH area. Therefore, the WHO recommended diagnostic concentration is no longer effective in controlling Ae. aegypti and Ae. albopictus larvae in these areas. Both the dengue vectors have evolved a high level of insecticide resistance to malathion and deltamethrin in the Gampaha District except Ae. albopictus mosquitoes in rural areas. Further, vectors in rural areas are indicated susceptible (>98%) to pyrethroids and emergence of resistance (<97%) for organophosphate insecticides. CONCLUSION: The results of this study warrant the vector management authorities on the proper application of insecticides and rational use in vector control. The susceptibility status of vector mosquitoes should be continuously monitored especially in dengue-endemic areas parallel to the routine surveillance programme. Further molecular studies are strongly recommended to determine the Knockdown Resistance (kdr) mutations among Aedes populations.